Mechanical and chemical element structures of sea urchin spines: specialization in ambulacral and interambulacral areas - Pathitta Suteecharuwat; Mayuka Arakawa; Yutaka Yoshida (PeerJ Materials Science)
Sea urchin spines are of interest for biomaterials and functional materials development due to their mechanical properties, which depend on their elemental composition. However, no previous study has examined the structural distinctions between the spines in the ambulacral and interambulacral areas. This study addresses that gap by investigating the structural and mechanical differences in the spines of Strongylocentrotus nudus, with a focus on these two areas. We used cantilever bending tests, Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), and inductively coupled plasma atomic emission spectroscopy (ICP-AES) to analyze the composition, elasticity, and microstructure of the spines. The bending modulus of elasticity was higher in the ambulacral area (52.067 GPa) compared to the interambulacral area (10.133 GPa), hardness and deformation. ICP-AES analysis revealed that ambulacral shaft had a slightly higher concentration of magnesium (Mg) (0.9844 wt%) compared to the interambulacral shaft (0.9804 wt%), while the calcium (Ca) concentration was lower in the ambulacral shaft (39.6578 wt%) compared to the interambulacral shaft (42.1076 wt%). Furthermore, a variation in Mg concentration was observed between the base and shaft parts of the spine. XRD showed a narrower (104) lattice spacing in the ambulacral spine (3.0264 Å) compared to the interambulacral spine (3.0275 Å), correlating with higher Mg concentration. These compositional and structural differences suggested that S. nudus modulates Mg concentration in calcite to achieve functional specialization of spines for locomotion and defense. Our findings may be useful for the development of novel functional materials.